How Information Sources Shape Destination Image and Visit Intention: A PLS-SEM Study of the Meneng Steppe, Mongolia - Undrakhgerel Ishdorja; Enkhbold Chuluunbaatarb; Damdinsuren Tseveendorj (Growth: Journal Management and Business, 2026)
Understanding how destination image is formed and how it influences visit intention is critical for emerging tourism destinations. This study investigates how information sources shape cognitive, affective, and overall destination image, and how these dimensions influence visit intention in the context of the Meneng Steppe, Mongolia. A conceptual model based on destination image theory was tested using data collected from 303 non-visitors through an online survey. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that information sources significantly affect cognitive, affective, and overall image. Cognitive image emerged as the strongest predictor of visit intention, followed by overall and affective image. Mediation analysis confirms that cognitive, affective, and overall image fully mediate the relationship between information sources and visit intention, as indicated by VAF values, meaning that information sources influence visit intention entirely through these destination image dimensions. This study contributes by validating a multi-dimensional destination image framework in an underexplored context and highlights the importance of digital information sources. Practically, the findings suggest prioritizing social media-driven strategies for effective destination branding.